Louis Althusser’s critique of the Communist Party and the question of the postrevolutionary state - Nowak, Jörg (Taylor & Francis, 2017)
This essay explores some aspects of the debate led by Louis Althusser and Etienne Balibar on the strategy of the French Communist Party (PCF) in the 1970s. They saw the Euro-communist turn of the party as a strategy that accepted the influence of social democrats without addressing the crucial question of mass participation in the party. Their criticism of the PCF was also a criticism of the statist strategy in socialist countries at that time, which they saw as a fusion of the socialist state with the working-class party. Althusser radicalized his stance when he demanded that a revolutionary party should stay outside the state, both before and after a socialist revolution. In this text, the references made by Balibar and Althusser to works of Marx and Engels are compared with the political positions developed in the original texts, and some conclusions for contemporary political strategies are hinted at.